Galeri Seni Rupa Di Pekanbaru Dengan Pendekatan Arsitektur Organik - Isrina Indah; Wahyu Hidayat; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Connoisseurs of artwork of Pekanbaru is out a lot. It could be seen from the enthusiasm that people show in many artwork activities, such as exhibitions that were usually being held in malls and hotels. However, art connoisseurs have to move from places to places to enjoy the art itself. This phenomenon shows that there is a lack of resources to satisfy people needs in facilitating these artwork. Therefore, a design of Fine Art Gallery wouldoffer its benefit to appease art connoisseurs in Pekanbaru. According to Frank Lloyd Wright, Organik Architecture is a philosophy that emphasize the harmonious relation between human habitation and nature, and its well integrated of unity, harmony, and simplicity. A Compatibility of art is applied as concept, harmony is displayed and a set of categorized artactivities is established in the design of Gallery. Through that idea, a simple mass formation and an integrated circulation between mass formation would be obtained.Keywords: Fine Art Gallery, Organic Architecture, Compatibility of Art